FRI0389 Foot involvement in patients with systemic sclerosis: a single-centre report. (15th June 2017) - Cuomo, G; Ruta, D; Frongillo, E; Pirro, L; Mastro, A Del; Romano, C
Abstract : Background: Foot involvement can be a source of morbidity and disability in patients with systemic sclerosis (SSc). Some studies have previously reported severity, echographic and radiographic manifestations of foot involvement in SSc (1, 2). Objectives: The aim of our study was to assess the nature and prevalence of foot problems in patients with SSc reporting a single centre experience. Methods: A podiatrist and a rheumatologist assessed 81 (76 female) consecutive patients attending our SSc outpatient clinic. The mean age was 50 years (range 21–70). Thirteen (16%) had diffuse cutaneous SSc with a median disease duration from Raynaud's Phenomenon of 5 years (range 3 –19); 68 (84%) had limited cutaneous SSc with a median disease duration of 11.5 years (range 1–41). The overall median disease duration was 11 years (range 1–41). Thirty (37%) were anticentromere antibodies positive, thirty five (43%) anti-scl70 antibodies positive. The two investigators evaluated the presence of the following features: colour changes, pain, previous ulceration, current ulceration, pre-ulceration (discoloration and thinning of the skin), toenail changes, hyperkeratosis, calcinosis, onychomycosis, dry skin, skin sclerosis, warts, scleredema, flatfoot. The presence of paresthesias, cramps, metatarsalgia were also investigated. Results: The diagram reports the prevalence of foot manifestations in the 81 SSc patients. Most SSc patients suffer from symptoms related to their feet, particularly dry skin (70%), hyperkeratosis (plantar 58%, finger V 63%), Raynaund's phenomenon (59%), cramps (55%). No statistically significant differences were found between diffuse and limited SSc groups. Conclusions: Our study suggests that, in patients with SSc, foot problems are common and potentially disabling. A careful assessment of the feet should always be performed in these patients, in order to identify problems at an early stage. References: La Montagna G et al. Semin Arthritis Rheum 2002. Sari-Kouzel H et al. Rheumatology (Oxford) 2001. Disclosure of Interest: None declared